(untitled) (Revista Electrónica REDINE, 2024)
The purpose of this essay was to reflect on the investigative skills used by committed professionals must have, which help students improve their academic performance, raising intellectual potential, where a social and scientific impact is achieved by developing human talent. Intrinsic in every university student and adult. The theoretical contributions of: Espinoza, Rivera and Tinoco (2015), Jericó (2001) and Parra (2021) were taken into account. This essay was developed from the methodological perspective of documentary research, with a qualitative approach and under the interpretive paradigm. We reflect that investigative competencies generate significant learning in terms of knowledge, attitudes, skills and values, which form them in a comprehensive manner and will allow them to perform and solve shortcomings and deficiencies in the work setting; and personally apply everything learned during life. Universities have the challenge of promoting human talent.